2016
DOI: 10.21037/atm.2016.11.82
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenases in cancer stem cells: potential as therapeutic targets

Abstract: Resistance to current chemotherapeutic or radiation-based cancer treatment strategies is a serious concern. Cancer stem cells (CSCs) are typically able to evade treatment and establish a recurrent tumor or metastasis, and it is these that lead to the majority of cancer deaths. Therefore, a major current goal is to develop treatment strategies that eliminate the resistant CSCs as well as the bulk tumor cells in order to achieve complete disease clearance. Aldehyde dehydrogenases (ALDHs) are important for mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
149
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 73 publications
1
149
0
Order By: Relevance
“…ALDHs such as the 1A3 isoform could be a key player in such therapeutic intervention. However, as we [45] and others [46,87,222] have discussed previously, the expression of ALDHs in normal tissue expression remain a stumbling block towards a credible clinical therapy. However, advances in drug delivery technologies could in the future enable administration of an ALDH inhibitor, which is potently selective for a specific isoform.…”
Section: Aldh Hypoxia and Tmementioning
confidence: 82%
“…ALDHs such as the 1A3 isoform could be a key player in such therapeutic intervention. However, as we [45] and others [46,87,222] have discussed previously, the expression of ALDHs in normal tissue expression remain a stumbling block towards a credible clinical therapy. However, advances in drug delivery technologies could in the future enable administration of an ALDH inhibitor, which is potently selective for a specific isoform.…”
Section: Aldh Hypoxia and Tmementioning
confidence: 82%
“…Some recent studies have shown dual expression of ALDH1 with CD44 (ALDH1 + CD44 + ) or CD133 (ALDH1 + CD133 + ) in primary ovarian tumour samples and linked that with reduced disease-free and overall survival in OC patients [215][216][217][218]. ALDH1 promotes tumour cell survival by reducing the in vivo cytotoxic damage induced by the oxidized aldehydes [218,219]. The enzyme also detoxifies residual cytotoxic materials left after chemotherapy treatment conferring resistance to ALDH1 + cells [218,219].…”
Section: Csc-based Therapymentioning
confidence: 99%
“…ALDH1 promotes tumour cell survival by reducing the in vivo cytotoxic damage induced by the oxidized aldehydes [218,219]. The enzyme also detoxifies residual cytotoxic materials left after chemotherapy treatment conferring resistance to ALDH1 + cells [218,219]. Few recent studies have explored ALDH as an attractive antigenic target for inducing ALDH specific immune responses [220].…”
Section: Csc-based Therapymentioning
confidence: 99%
“…RA signaling is critical for the transcriptional control of many genes, and ALDH1A enzymes have received attention as potential drug targets. 2–7 …”
mentioning
confidence: 99%